Spontaneous Hemoperitoneum Masquerading Placental Abruption: A Case Report - Subedi, S; Banerjee, B (Nepal Journal of Obstetrics and Gynaecology, 2014)
Hemoperitoneum during pregnancy is a rare but potentially life threatening condition to both mother and fetus. Spontaneous hemoperitoneum may develop from rupture of various abdominal or pelvic viscera like spleen, pancreas and also uterus from the uterine ovarian vessels and rarely from pelvic endometrial implants. It mimics placental abruption having similar clinical presentation like acute abdominal pain, peritonitis, shock and fetal distress or fetal death. We present a case of spontaneous rupture of superficial uterine vessels in third trimester of pregnancy with an objective to share our experience in managing this rare emergency condition having diagnostic dilemmas. DOI: http://www.dx.doi.org/10.3126/njog.v7i2.11145 Nepal Journal of Obstetrics and Gynaecology / Vol 7 / No. 2 / Issue 14 / July-Dec, 2012 / 50-51